2011
DOI: 10.4038/sjae.v4i0.3488
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Technical Efficiency and It's Determinants in the Tea Small Holding Sector in the Mid Country Wet Zone of Sri Lanka

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 6 publications
8
35
1
2
Order By: Relevance
“…Farmers with much experience in tea farming can produce more output with given inputs as compared to those with less experience. This result is consistent with the finding of Basnayake et al (2000).…”
Section: Factors Affecting Resource Use Efficiencysupporting
confidence: 83%
See 1 more Smart Citation
“…Farmers with much experience in tea farming can produce more output with given inputs as compared to those with less experience. This result is consistent with the finding of Basnayake et al (2000).…”
Section: Factors Affecting Resource Use Efficiencysupporting
confidence: 83%
“…Since tea production is mono crop farming and frequently affected by weather conditions, diseases, and other exogenous random factors (noise effects), stochastic frontier analysis was applied for this study to distinguish noise effects and inefficiency effects in the model. In recent years, there have been some studies on tea production efficiency estimation in developing countries (Basnayake & Gunaratne, 2000;Baten et al, 2010;Haridas et al, 2012), particularly in Vietnam such as Saigenji and Zeller (2009). By using stochastic frontier analysis, all these studies showed clearly output-oriented technical efficiency of tea production which determined tea farms' possibility to maximize output levels with given set of inputs, but their limitation were not to estimate the input-oriented technical efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The computed mean technical effi ciency of this survey was lower compared to the technical effi ciency of 83.1% observed by Basnayake and Gunaratne (2002) in the Tea Smallholding…”
Section: Determining Technical Effi Ciencycontrasting
confidence: 70%
“…Other studies on productivity of crops in Sri Lanka such as for rice (Shantha et. al., 2012), tea (Basnayake and Gunaratne, 2002) and Potato (Amarasinghe and Weerahewa, 2001) has revealed that land is a significant factor of production. In this regard, consolidation of fragmented smallholder land holdings through collective farming or group farming would be a feasible option for consideration to reap the benefits of economies of scales in maize production.…”
Section: Discussionmentioning
confidence: 99%